2023
DOI: 10.1142/s0218625x23500415
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Optimization of Process Parameters of the Piston Alloy-Based Composite Produced by FSP Using Response Surface Methodology

Abstract: In this paper, A356/B4C composites were fabricated using the friction stir processing (FSP) method. The process’s input parameters, including rotational and transverse speed, were optimized using the response surface methodology (RSM). Three factors and three levels with nine experimental runs made up the design of the experiments. An analysis of variance (ANOVA) was employed to determine whether the constructed model was adequate at a 95% confidence level. This study found that transverse speed was the most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Thus, severe plastic deformation (SPD) technologies have attracted more attention to studying the wear phenomenon and tribological mechanisms. Many of these technologies have been used, including equalchannel angular pressing (ECAP) [21], friction stir processing (FSP) [22], high-pressure torsion (HPT) [23,24], and other techniques. The authors suggest the possibility of exploring these techniques to improve the properties of materials and wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, severe plastic deformation (SPD) technologies have attracted more attention to studying the wear phenomenon and tribological mechanisms. Many of these technologies have been used, including equalchannel angular pressing (ECAP) [21], friction stir processing (FSP) [22], high-pressure torsion (HPT) [23,24], and other techniques. The authors suggest the possibility of exploring these techniques to improve the properties of materials and wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the relationship between the steering gear and propeller was analyzed, as it directly affects the ship's speed and direction. To provide the controller with an accurate representation of the ship's operation and enable the testing of new control methods, the mathematical model was further refined to isolate the components that exclusively affect the course of the ship, such as the rudder, propeller, and hydrodynamic forces [3]. Test experiments were conducted on actual ships, and simulation techniques were utilized to determine the parameters of the model.…”
Section: Introductionmentioning
confidence: 99%
“…The results concluded that ANN was effective enough to provide a correlation between input and output parameters, whereas multiobjective optimization provided optimized FSW parameters. Similarly, Akbari et al [8,9] fabricated aluminum-based composites using FSW, optimized the parameters using RSM, and ANOVA, and numerically simulated the process using the 3D FEM process. These advanced simulations and software helped researchers determine better working parameters and conditions without performing bulk experimentations.…”
Section: Introductionmentioning
confidence: 99%